Enhancing Students’ Conceptual Understanding of Colloidal Systems through Inquiry-Based Chemistry Instruction - Rajendra Nivrutti Shirsat; Sang Yeon Lee (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to examine the effect of inquiry-based chemistry learning on secondary school students’ conceptual understanding of colloidal systems. Methodology: A quasi-experimental design employing a pretest–posttest control group was used. Data were collected using a validated conceptual understanding test and a diagnostic questionnaire. The data were analyzed using N-gain analysis and an independent samples t-test at a 0.05 significance level after confirming the assumptions of normality and homogeneity. Main Findings: The results indicate that inquiry-based learning significantly improved students’ conceptual understanding. A total of 67.5% of students achieved scores above the minimum competency standard, while 92.5% demonstrated a moderate level of conceptual improvement. The t-test results (t₍calculated₎ = 4.84 > t₍table₎ = 2.68) confirmed a statistically significant difference between pretest and posttest scores. Novelty/Originality of this study: The novelty of this study lies in the application of a contextually adapted guided inquiry model supported by validated diagnostic instruments. This approach provides robust empirical evidence on how inquiry-based learning facilitates students’ construction of chemical concepts, thereby contributing to both theoretical and practical advancements in chemistry education.